Synthesis and Characterization of Nickel-Based Superalloy Materials for Manufacturing Aircraft Turbine Blades - Ruzuqi, Rezza; Rudyardjo, M.Si., Drs. Djony Izak; Zaidan, S.Si., M.Si., Ph.D., Andi Hamim (Indonesian Applied Physics Letters, 2021)
The research has been conducted to manufacture nickel-based Superalloy materials. The purpose of this research was to find out the effects of variation of nickel composition on physical and mechanical properties of the Superalloy materials and find out the appropriate composition of Superalloy materials as materials for turbine blades. This research used nickel, cobalt, chromium, molybdenum, aluminium, and titanium commercial. The results showed that with more addition of nickel composition, the density and hardness values increased. This research showed that nickel-based Superalloy material 59 wt% was better applied as materials for turbine blades. It is also supported by the results of the test microstructure, where the structure of the sample morphology is more delicate and denser and contains smaller pores. Based on the XRD test results are also shown in the sample has been formed Superalloys phase.